2018
DOI: 10.1016/j.jsxm.2018.01.024
|View full text |Cite
|
Sign up to set email alerts
|

A New Technique for Coronaplasty in Penile Reconstruction

Abstract: Background The coronaplasty is an important step of the phalloplasty procedure as it creates a prominent coronal ridge and a constricted coronal sulcus, resulting in the transformation of a regular skin flap into a flap resembling a circumcised penis. Aim The aim of this article is to describe our new coronaplasty technique that exploits opposing contracting forces of 2 different skin grafts to hold the shape of a thick, dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 13 publications
0
8
0
3
Order By: Relevance
“…In the mandatory primary imitation of the external urethra and the coronary sulcus, 27 the simple steps do not lengthen the operative time (performed in parallel with the closure of the donor back defect) and provide the neophallus a natural shape and appearance, which is extremely beneficial for the patient’s psychological well-being (especially important for transgender patients) and directly affects the quality of their social rehabilitation. 28 Our experience has demonstrated that an aesthetic and authentic appearance of the neophallic external urethra imitation in 20% of cases may lead to abandonment of the second urethroplasty step.…”
Section: Discussionmentioning
confidence: 99%
“…In the mandatory primary imitation of the external urethra and the coronary sulcus, 27 the simple steps do not lengthen the operative time (performed in parallel with the closure of the donor back defect) and provide the neophallus a natural shape and appearance, which is extremely beneficial for the patient’s psychological well-being (especially important for transgender patients) and directly affects the quality of their social rehabilitation. 28 Our experience has demonstrated that an aesthetic and authentic appearance of the neophallic external urethra imitation in 20% of cases may lead to abandonment of the second urethroplasty step.…”
Section: Discussionmentioning
confidence: 99%
“…The Norfolk technique, which builds on Munwar’s original method but integrates a skin graft, is currently most popular, due to its ability to create a circumcised appearance of the glans with low complications. Other procedures, such as the Gottleib design 7 (to improve pigmentation) and various alternative methods of coronaplasty, 2 , 4 , 8 have been described to optimize the results of the classic Norfolk technique. Still, none yet seem to be provably superior to the base concept of Norfolk: a distal skin ridge folded over with a more proximal skin graft, and a skin graft proximal to this to cover the defect left by the glans creation.…”
Section: Discussionmentioning
confidence: 99%
“…An incision is made at the appropriate point at the distal phallus and the distal phallus skin flap developed as the gland ridge, as described in most glansplasty techniques. [1][2][3][4] A 100% medical-grade silicone carving block is used to create a hand-carved glans ridge implant of the correct length, tapered at both ends. It is generally 5 × 5 mm in maximum thickness and triangular in cross section (Fig.…”
Section: Surgical Techniquementioning
confidence: 99%
“…Diese kann auf Wunsch der Patienten unabhängig von der Art der durchgeführten Phalloplastik durch die Konstruktion eines Sulcus coronarius gebildet werden (▶Abb. 4) [49,81]. Die Sulcuscoronarius-Plastik kann bei axial gestielten Lappenplastiken wie der Radialislappenplastik simultan zur Phalloplastik erfolgen.…”
Section: Glansplastikunclassified